(untitled) (International Seven Journal of Multidisciplinary, 2023)
The genetic content of a person determines his characteristics and his process of evolution. However, in addition to the hereditary factor, it is verified that there is influence of the cultural environment and the level of harmonious integration of the child with the world in its surroundings on the development of the same, which is the object of study of Psychopedagogy. It is a discipline of the Human Sciences, whose beginning took place in the nineteenth century, with the demographic expansion of the post-war period, but its importance is extremely high for the present day, in which there is the search for a better orientation of knowledge and a deeper maturation of human learning. Psychopedagogy is a systematic study, closely linked to psychoanalysis and medicine, on the conditioning factors of behavior and lifestyle and their influence on human development in its most varied aspects, from cognitive functions to social interactions. The work of the psychopedagogue is to contribute to the optimized school formation of students through methods developed for each specific case. Through the interventions of the psychopedagogue in the educational process, it is possible to reverse learning deficits, help the inclusion of children with special needs and improve the social integration of the student in the environment in which he is inserted. The objective of the bibliographic research is to analyze the true contributions of psychopedagogy to education and to enumerate the main challenges experienced by the professional in the school institution. The bibliographies used are scientific and review articles, monographs and dissertations that report the performance of the psychopedagogue in the educational field. In this way, the work emphasizes the mission of the psychopedagogue, which is to contribute so that all individuals can assimilate contents and learn efficiently and effectively, promoting means of obtaining a healthier and more complete environment. human development, in addition to affirming the constant need for this professional in the educational environment.